Penerapan Hukum Pidana Terhadap Warga Negara Asing Yang Melakukan Kejahatan Skimming Di Indonesia - Heidy Esmeralda Silooy; Juanrico Alfaromona Sumarezs Titahelu; Denny Latumaerissa (Faculty of Law Universitas Pattimura, 2023)
Skimming is the act of stealing ATM card information by taking information contained on the magnetic stripe on the card illegally, skimming crimes are committed by installing skimmer devices on ATM machines to obtain data on ATM cards. Skimming crimes are inseparable from the various methods used by the perpetrators, the perpetrator of skimming crimes is a foreign national. Crimes are committed professionally and well organized so that it is easy to commit skimming crimes as a result of skimming crimes there are many losses to customers and banks. Purposes of the Research: to determine the application of criminal law against foreign nationals who commit skimming crimes. Methods of the Research: The type of research used in this research is normative juridical. This type of research is descriptive analytical research. The sources of legal materials are primary, secondary and tertiary legal materials. Data collection techniques are carried out through tracing legal materials by reading, seeing, listening, or doing. Results of the Research: Skimming crimes regulated in the Criminal Code and the ITE Law in which the elements in Article 30 of the ITE Law on illegal access have been fulfilled by skimming crimes, namely the element of every person, the element intentionally, the element without the right or against the law and the element of accessing a computer or electronic system. In addition, the results of this study explain that the skimming crimes of the perpetrators are punished based on existing laws in accordance with what has been done, the application of criminal law is of course as a legal provision in tackling crime, anyone who commits a crime will be punished according to applicable law whether it is an Indonesian citizen or a foreign citizen. In addition, the crimes committed can be seen based on the applicable principles relating to skimming crimes are territorial principles or regional principles because legal provisions apply to everyone who commits a crime in the territory of the Republic of Indonesia must be punished according to existing regulations.